Identification of Adults’ Attitudes Towards Earthquake - Efe Gençler; Özlem Sinan (Global Nursing Insights, 2026)
Aim: The present study aimed to determine the adults’ attitudes towards earthquakes and the influencing factors of attitudes towards earthquakes.Material and Methods: This was a descriptive cross-sectional study. The sample of the study consisted of 466 adults selected using a cluster sampling method from two different neighborhoods in a city in Türkiye. Data were collected using a questionnaire based on relevant literature and the Attitudes Towards Earthquake Scale. The descriptive statistics were used in the analysis of the study data.Results: The mean total score of the participants on the attitudes towards earthquake scale was found to be 170.71 ± 14.86. Gender, marital status, age, having children, and desire to receive earthquake education were statistically significantly associated with attitudes (p